Position of enigmatic miniature trichomycterid catfishes inferred from molecular data (Siluriformes). (25th October 2017) - Henschel, Elisabeth; Mattos, José Leonardo O.; Katz, Axel M.; Costa, Wilson J. E. M.
Abstract : Trichomycteridae is a well‐corroborated catfish family that comprises about 300 valid species distributed in eight subfamilies. The phyletic status of the Trichomycterinae is uncertain, with different hypothesis regarding the position of the miniaturized Trichomycterus hasemani group. This group comprises four valid species, and neither its monophyly nor its positioning among the Trichomycteridae was tested in a phylogenetic framework. Bayesian Inference and Maximum Likelihood analyses of a molecular data set comprising the mitochondrial genes 12S and 16S and the nuclear genes H3, MYH6 and RAG2 (2983 bp) for 26 taxa highly supported the miniature catfish T. hasemani group as monophyletic and sister to the Tridentinae, consequently recognized as a new genus of this subfamily. Potamoglanis gen. nov. is diagnosed by seven character states: an angle of 35–40° between the main longitudinal axis of the head and the main axis of the autopalatine; thin tubular shape of the second ceratobranchial; presence of six or seven anal‐fin rays; eyes dorsally placed on head; opercular and interopercular odontodes patches not juxtaposed; absence of a distal process on the hyomandibula and presence of a long process on the anterior region of the hyomandibula. Potamoglanis gen. nov is similar to the Tridentinae genera by the presence of a wide cranial fontanelle; presence of a short ventral process in the opercular bone and by the origin of the dorsal fin placed in a vertical through the anal‐fin origin.